A first-principles understanding of the CO-assisted NO reduction on the IrRu/Al2O3 catalyst under O2-rich conditions. Issue 13 (21st June 2021) - Arshad, Malik Waqar; Kim, Dong Hun; You, Young-Woo; Kim, Soo Min; Heo, Iljeong; Kim, Seok Ki
Abstract : The IrRu alloy offered optimal energetics for NO reduction by CO. The ensemble effect plays a key role in promoting the reactivity of the IrRu alloy. Making the IrRu surface alloy is better for CO-SCR than forming an alloy over the bulk structure. Abstract : Controlling the surface composition of alloy catalysts can provide an opportunity to improve their activity and selectivity for a target reaction. However, since the various effects of alloys are often mixed, it is difficult to maximize the expected benefits of the alloy formation. In the present study, we prepared an IrRu bimetallic catalyst by using a wetness impregnation method and studied the reaction performance of NO reduction by CO in the presence and absence of O2 . A series of spectroscopic analyses confirmed the formation of the IrRu bimetallic alloy. Further, we investigate the active-site ensemble effect in the IrRu bimetallic catalyst that selectively reduces NO to N2 using CO as a reducing agent in the presence of excess oxygen. Mechanistic insight gained through the density functional theory calculations revealed that the IrRu alloy catalyst has moderate binding energies for all the adsorbates and intermediates, resulting in the acceleration of critical surface reactions, such as CO oxidation and N–NO disproportionation. In addition, a series of theoretical surface models suggest that the selectivity promotion on the IrRu alloy surface originates from the ensemble effect, while ligand and strain effects are detrimental to the catalyst performance. This study lays the foundation for the design of bimetallic catalysts that can provide maximal promotion of NO reduction with minimal use of precious metals.